The innovation, risk taking and proactiveness on performance of Smes in Nigeria, the moderating role of microfinance institute - Mahat, Fauziah; Zannah, Mohammed (International Organization of Scientific Research, 2021)
This study empirically examined the relationship between innovation, risk taking and proactiveness on performance of small and medium enterprises in Nigeria. And also moderating role of microfinance institute. 340 questionnaires were distributed to owner-manager of SMEs, 308 were successfully returned. Entrepreneur enhances the performance of small and medium enterprises performance through innovation, risk taking, and proactiveness. The study employs descriptive statistic Pearson correlation analysis to analysis the data. The result shows thesignificant and positive relationship between EO (innovation, risk taking and proactiveness) and performance of small and medium scale enterprises in Nigeria. Among the dimension of entrepreneur orientation, the research found that only innovation and proactiveness were astatistically significant predictor of small and medium scale enterprises in Nigeria, while risk taking found to be statistically not asignificant predictor. The implication of the finding and recommend made was discussed at the end.